Profitability, Growth and Competitiveness of Indian Steel Industry Constraints and Prospects Dr. Tarun Das - Dr. Tarun Das (Planning Commission, Government of India)
The vital role of Steel Industry for overall economic development of India makes the Study of productivity, performance and efficiency of the industry a subject matter of public debate, although not always well-informed and objective. Since independence Indian Steel Industry has made a considerable progress - capacity of crude steel production has increased from hardly 1 million ton (mt) to 15.5 mt and per capita consumption of steel has increased from 3 Kg to 19 Kg per annum. At present we have 6 integrated steel plants (Bhilai, Bokaro, Durgapur, IISGO, Rourkela and TISCO) with a capacity of 11.6 mt of crude steel per annum, 160 mini steel plants with a capacity of 4 mt (in terms of billets scrap production), more than 1000 billet/scrap rerolling units with a capacity of 6.3 mt (in terms of light merchant products) and 71 wire drawing units with a capacity of 0.84 mt.
Transport Modeling Unit, Planning Commission, Government of India
Keywords: Steel Industry